Kebijakan Ekonomi Luar Negeri China dari Masa ke Masa dan Ambisi Internasionalisasi BUMN China di Tangan Xi Jinping - Nur Arifin Rivai, Aspin (Jurnal Ilmiah Hubungan Internasional Fajar, 2022)
Contemporary China's economic growth has shown a prestigious, spectacular, and increasingly strategic position. This is due to the success of the Beijing’s administration in launching reforms program and open-door policy of the foreign economy in 1978. Based on this research, China's global initiation actually started with the vision and legacy of Deng Xiaoping's leadership, namely the policy of good neighbor relations which was in turn transformed by Xi Jinping through an assertive and ambitious style. This can be seen from the emergence of Belt and Road Initiative (BRI). This research shows that there are three factors underlying Xi Jinping's choice to formulate BRI as the foreign economic policy agenda. First, BRI is a reform in aligning cooperation and economic integration. Second, the emergence of BRI here is Xi Jinping's rationalization to avoid the risk of excess production capacity after the 2008 global financial crisis, so that BRI is used as a medium for relocating the excess capacity. Third, the emergence of BRI as a foreign economy policy is actually a continuation of the SOEs reform itself. That is, China's SOEs internationalization program must get a special arena through the full intervention of Xi Jinping.